Exploring Differences in Attachment and Love Styles Among Prostate Cancer Patients Undergoing Androgen Deprivation Therapy - Akhmad Miftahudin Fazri; Aaron Tigor Sihombing (http://dharmais.co.id/, 2026)
Background: Prostate cancer (PCa) is a prevalent malignancy in men, often treated with androgen deprivation therapy (ADT), which can lead to significant adverse effects, including changes in psychological well-being and relationship dynamics. This study explores how ADT affects attachment styles and love attitudes in PCa patients.Methods: This was a cross-sectional analysis involving PCa patients treated at the Department of Urology between July and October 2022. 150 patients completed questionnaires assessing demographic profiles, the Adult Attachment Scale (AAS), and the Love Attitude Scale (LAS). Data evaluation was executed using Kolmogorov-Smirnov, the Independent t-test, Pearson’s chi-square test, and the Mann-Whitney U test using IBM SPSS Statistics 26.Results: PCa patients undergoing ADT were compared with those not receiving ADT, with significant differences in education level, employment status, age, and marital duration (p < 0.05). PCa patients receiving ADT exhibited increased amounts of anxious (49.3%) and avoidant (48%) attachment styles compared to the non-ADT group, which showed a predominance of secure attachment (50.7%). The ADT group favored the Mania (22.7%) love style, while the non-ADT group exhibited Agape (34.7%) love styles. Statistical analyses revealed significant differences in attachment and love styles between the groups (p < 0.001).Conclusions: Prolonged ADT is associated with shifts towards insecure attachment and obsessive love styles, adversely affecting emotional well-being. Future research should focus on the role of testosterone levels in these dynamics.